ANALISIS STRATEGI PEMASARAN TERHADAP MINAT NASABAH PADA PERBANKAN DI PEMATANGSIANTAR - Sarida Sirait; Kalvin Sinaga (Politeknik Bisnis Indonesia, 2020)
Financial institutions, both bank and non-bank, which continue to develop in Indonesia will encourage financial institutions to always optimize their marketing activities. One of them is Bank Mandiri in facing competition. One of the strategies of Bank Mandiri is the marketing mix strategy. The formulation of the problem in this study is whether the Marketing Mix strategy affects the interest of Bank Mandiri KC Pematangsiantar customers. The purpose of this study is to determine whether the Marketing Mix affects customer interest in Bank Mandiri KC Pematangsiantar. This research is a type of field research (field research) with a descriptive nature using primary and secondary data, in addition to the data collection methods in this study using observation and interview methods, and this method of analysis using quantitative analysis methods. Based on the results of this study, it shows that the application of marketing strategies uses a marketing mix, the products offered are very varied according to the needs of society for the present and the future, then promotion using personal selling, advertising via television, brochures and others. , publicity with exhibition activities, social service. The marketing strategy that has been implemented has been good in increasing customer interest. Respondents in this study were 97 customers. From the results of data analysis it can be concluded that, there is a significant positive influence between marketing strategy variables (X) on customer interest (Y) at Bank Mandiri Kc Pematangsiantar, the contribution of the influence of marketing strategy variables (X) on customer interest (Y) coefficient of determination (R2) 0.76 shows that 76% of marketing strategies (X) affect customer interest (Y), while 24% are influenced by other variables not discussed in this study.